Methods to improve our field - Hill, Aaron D.; McKenny, Aaron F.; O'Kane, Paula; Paroutis, Sotirios (Bingley, U.K. : Emerald Publishing Limited, 2023)
Research Methodology in Strategy and Management advances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed. Offering innovative ideas that explore how strategy and management methodology can be developed, the chapter authors in Volume 14, Methods to Improve Our Field, consider approaches that range from the re-imagining of secondary data in the digital age and Interpretive Phenomenological Analysis (IPA) to Machine Learning and Artificial Intelligence. Methods to Improve Our Field is a necessity for both academics and researchers interested in the progression and cutting-edge studies of management, strategy, international business, entrepreneurship, and organization theory.
Chapter 1. Introduction to methods to improve our field / Aaron D. Hill, Aaron F. McKenny, Paula O'Kane, and Sotirios Paroutis -- Chapter 2. Reimagining secondary data in a digital age / Katrina Pritchard -- Chapter 3. Insights from the application of interpretative phenomenological analysis in management research / Yulia Taylor and Fiona Edgar -- Chapter 4. Synthesizing best practices for conducting dictionary-based computerized text analysis research / Shane W. Reid, Aaron F. McKenny, and Jeremy C. Short -- Chapter 5. Using mixed effect growth models to examine time as a predictor of interest and between-firm differences over time / Donald J. Schepker and Paul D. Bliese -- Chapter 6. Garbage in, garbage out: A theory-driven approach to improve data handling in supervised machine learning / Steven J Hyde, Eric Bachura, and Joseph Harrison -- Chapter 7. Artificial intelligence and operationalization of psychological constructs: The case of emotions and emotional authenticity of entrepreneurs during pitch presentations / Andreas Schwab, Yanjinlkham Shuumarjav, Jake B. Telkamp, and Jose R. Beltran -- Chapter 8. Pechakucha-based participatory video for organizational research / Timothy Madden, Laura T. Madden, and Anne D. Smith.
Includes bibliographical references and index.
Print version record.
Keywords: elektronické knihy; electronic books; Management -- Research -- Methodology; Business planning -- Methodology; Business & Economics -- Management Science; Organizational theory & behaviour